The effectiveness of cooperative learning in enhancing communication: an experimental study / Nor 'Azah A. Aziz - A. Aziz, Nor 'Azah (2006)
The purpose of this study was to find the effectiveness of using cooperative learning strategies in enhancing communication among rural students. A pre-test and post-tests were conducted on a particular group of students in this research project. In addition, questionnaires was administered to find the teachers’ and students’ opinion on the use of cooperative learning in the teaching and learning process. The findings of this study revealed that the experimental group performed better in their post-test individually or in their group. In spite of this, when their performance as individual were compared to their performance in the group, it showed that their performance in groups were better. Overall, their score for post-test increased compared to their pre-test. It proved that cooperative learning strategies have a certain degree of influence on the students’ academic performance. It also showed that this student-centered approach can give positive results to the rural students, to improve their performance in second language learning.